KEPENTINGAN INDONESIA MENJALIN HUBUNGAN KERJASAMA MILITER DENGAN TURKI TAHUN 2010-2014 - Sapta Berysta (HI 16 UMY, 2016)
The title of this research is "The interests of Indonesia Relationships military cooperation with Turkey in 2010-2014". Turkey has a highly developed defense industry considering the strategic location of Turkey's borders with the countries of Asia and Europe. Because the position sandwiched between many countries and potential conflicts at the border, the Turkish defense industry to develop highly advanced. In analyzing the use of Decision Making Theory of Foreign Affairs William D.Coplin. Methods of data collection through library research (library research). The data collected will be processed qualitatively and using deductive method. Results of the research interests of Indonesia to Connect Military Cooperation With Turkey influenced by the political situation in the country, namely the approval of Parliament for military cooperation with Turkey through Law No. 14 Year 2014 concerning military cooperation with Turkey. Second, the economic factor which is of economic interest of this cooperation as a link economic cooperation with Turkey and aims to increase Turkish investment in Indonesia and to absorb the labor force in the country in order to produce the means of defense used in many countries. Factors Indonesian military interests military cooperation with Turkey is providing various facilities required in a joint research began development, production and modernization projects, mutual assistance in the field of production and procurement of industrial products manufacture of defense services and cooperation in the field of defense industry cooperation. Secondly, the cooperation agreement in the field of industrial land dimension between PT. PINDAD cooperation with FNSS Defence System Inc. Indonesia chose Turkey and FNSS because of the experience and advanced technology in this field has been recognized internationally. With military cooperation with Turkey is expected to absorb the increase of military equipment to meet national needs. Policy of military cooperation with Turkey is pleased to transfer technology, the transfer of technology in the field of Indonesian military can increase the ability of military technology independently. The interests of cooperation with Turkey can help modify maritime patrol aircraft, as well as get components or parts for F16 fighter aircraft that do not depend on the United States. Keyword: National Interest, Cooperation, Military